First record of stenogastric Corotoca Schiødte (Staphylinidae, Aleocharinae, Corotocini) with notes on behavior, morphology and its phylogenetic significance - Pires-Silva, Carlos Moreno; Zilberman, Bruno; Eloi, Igor; Bezerra-Gusmão, Maria Avany (Zootaxa, 2019)
Physogastric rove beetles are usually studied in an aspect of the physogastry concept, which is defined as the enlargement of membranous parts of abdomen. This feature along with lack of the secondary sclerotization is used to differentiate physogastric from stenogastric individuals. Charles H. Seevers was the first author to record that the differences between physogastric and stenogastric rove beetles represent more than merely body size difference and that the secondary sclerotization, which occurs during the post-imaginal growth, leads to differences beyond that matter. Herein, we record the first stenogastric Corotoca specimen, and the morphological and behavioral differences of physogastric individuals are discussed. It is concluded that stenogastric individuals have features that may have useful implications for phylogenetic and taxonomic studies.